Cigarette smoking, coffee consumption, alcohol intake, and clozapine metabolism: A Mendelian randomization study - Zeng, Lingsi; Lv, Honggang; Li, Juan; Xue, Ranran; Liu, Xia; Zhou, Cong; Yu, Hao (Frontiers in Psychiatry, 2022)
Background: Clozapine is an effective antipsychotic medication for patients with treatment-resistant schizophrenia. Previous studies revealed that smoking, alcohol intake, and coffee consumption altered the metabolism of clozapine. However, causal associations between substance use and clozapine levels were not sufficiently established. Methods: Several genome-wide association studies provided genetic tools for six measures of substance use, including age of smoking, cigarettes per day, smoking cessation, smoking initiation, coffee consumption, and alcohol consumption (GWASs). Utilizing the CLOZUK consortium's dataset, their associations with clozapine and its metabolite concentrations were evaluated. All GWAS data were collected from the European population. Inverse variance weighted (IVW) meta-analysis was used with complementary methods (e.g., weighted median and MR Egger) to combine Mendelian randomization (MR) estimates from each genetic instrument. Additionally, we employ various sensitivity analyses to investigate horizontal pleiotropy and heterogeneity. Results: Genetically predicted level of smoking initiation was significantly associated with clozapine (β=-0.14, P=4.53E-04) concentrations and norclozapine concentrations (β=-0.14, P=3.33E-04), and coffee consumption was significantly associated with clozapine econcentrations (β=-0.42, P=1.70E-14), norclozapine concentrations (β=-0.27, P=1.51E-07), and the metabolic ratio of clozapine to norclozapine (β=-0.15, P=5.35E-07), survived after the Bonferroni correction (P=0.05/6=0.008). In sensitivity analyses, the weighted median and MR Egger methods demonstrated directionally consistent effects. In addition, our sensitive test indicated no significant horizontal pleiotropy and heterogeneity (P > 0.05). However, other measures of substance use (age of initiation smoking, cigarettes per day, smoking cessation, and drinks per week) were not associated with clozapine metabolism. Conclusion: Our investigation revealed a correlation between greater nicotine intake and coffee consumption and reduced blood levels of clozapine and norclozapine. providing clinicians with guidance on how to adjust clozapine levels for clozapine-treated patients.